Synergistic cardioprotective effects of melatonin and deferoxamine through the improvement of ferritinophagy in doxorubicin-induced acute cardiotoxicity - Hanna, Mira; Seddiek, Hanan; Aboulhoda, Basma Emad; Morcos, George N. B.; Akabawy, Ahmed M. A.; Elbaset, Marawan Abd; Ibrahim, Abdelsatar Abdelsatar; Khalifa, Mohamed Mansour; Khalifah, Ibtesam Mahmoud; Fadel, Mostafa Said; Shoukry, Tarek (Frontiers in Physiology, 2022)
Ferritinophagy is one of the most recent molecular mechanisms affecting cardiac function. In addition, it is one of the pathways by which doxorubicin, one of the anticancer drugs commonly used, impacts the cardiac muscle negatively, leading to cardiac function impairment. This side effect is tying hands towards the use of doxorubicin. Iron chelators play an important role in hindering ferritinophagy. Antioxidants as well can impact ferritinophagy by improving oxidative stress. In this study, it was assumed that the antioxidant function of melatonin could promote the action of deferoxamine, an iron chelator, at the level of ferritinophagy. Forty-two male Wistar rats (150–200 g) were divided into seven groups (n = 6) which consisted of group I: control normal, group II doxorubicin (Dox), group III: Melatonin (Mel), group IV: Deferoxamine (Des), group V: Mel + Dox, group VI: Des + Dox, and group VII: Me + Des + Dox. Group III and IV animals were orally pretreated with Melatonin 20 mg/kg/day for seven days. Group IV and VI were treated with deferoxamine at a 250 mg/kg dose once on D4 before Dox was given. Doxorubicin was given 20 mg/kg ip single dose. On the 8th day, the rats were lightly anaesthetized for ECG analysis and Echocardiography. Serum samples were collected and then sacrificed for tissue sampling. The following biochemical assessments were done: PCR of NCOA4, IREB2, FTH1, SLC7A11 and GPX4; ELISA for serum cTnI, serum transferrin, tissue GSH and MDA. In addition, Histopathological assessment of heart injury; immunostaining of Caspase-3, Bax, and Bcl2; and physiological function assessment using ECG and ECHO. Doxorubicin-induced acute significant cardiac injury with increased ferritinophagy and apoptosis that responded to single and combined prophylactic treatment in which the combined treatment showed mostly the best results. In conclusion, using melatonin as an antioxidant with an iron chelator, deferoxamine could hinder the hazardous cardiotoxic effect of doxorubicin. However, further studies are needed to detect the impact of higher doses of Melatonin and Deferoxamine with a prolonged treatment period.